The development, validation and implementation of a data acquisition system to quantify in-field tractor performance characteristics - Owen, Dalton (Kansas State University, 2019)
In the agriculture industry, in-field efficiency of tractors is critical information for operators and producers. Properly matching tractor to implement using real-world tractor performance characteristics is the primary factor that effects in-field efficiency. Currently, tractor testing is primarily conducted in a controlled lab environment to quantify attributes such as power take-off (PTO) power and fuel consumption. However, in-field quantification of these attributes is necessary to gain a full understanding of the machine’s performance. Therefore, this study was conducted with two primary objectives: 1) develop a data acquisition system to measure real-time tractor performance at varying machine states during field operations, and; 2) evaluate the performance of tractors individually and compared to each other. Studies were conducted to test multiple different sized tractors with varying implements used in a specific crop production cycle; these tractors included two smaller 71 HP machines, a 90 HP and a 100 HP machine. The primary performance comparison goals were to evaluate the performance efficiency differences between a cabin and open station machine of the same size, and to evaluate the differences in performance between two similarly sized machines. A custom data acquisition (DAQ) system developed comprises of a torque sensor, flow meter, and GPS to acquire target performance parameters using a National Instruments cRIO system. The PTO torque sensor and fuel flow meter were tested and validated in a controlled lab using a PTO dynamometer and fuel scale. Validation field studies conducted showed that the DAQ system captured real-time performance parameters; strong correlation was observed between power, speed, and fuel consumption.   Using the real-time data allows for a better understanding of the relationship between machine and implement, as well as a more thorough understanding of the effect of terrain and crop load on fuel consumption and PTO power. The peak torque values through the implement drivetrain and their frequencies coupled with the average breakdown of power consumption by the implement gives the manufacturer and producer the opportunity to modify usage trends or design, respectively. Spatial fuel consumption data on a tractor by tractor basis allows varying machines to be compared directly based on their efficiency. Testing of the two smaller tractors took place on the same day in a uniform field. While the data did not indicate any difference between open station and cabin machines, strong correlation was observed between both operating speed and PTO mode selection and performance efficiency. The testing of the two larger tractors was done on sequential cuts of alfalfa on the same field; to account for this, bales were geotagged and weighed to produce a forage density map. Data from testing yielded two main results; the first being that the fuel consumption rate of each tractor and operation can be accurately predicted using an equation using PTO power and operating speed as variables. The equation that defines the fuel consumption for the swathing operation predicts the fuel consumption within 10% over 75% of the time in both sized machines. Data recorded by the DAQ system yields the information necessary to give the manufacturer a thorough understanding of how machines and implements interact with each other, as well as how external factors effect machine performance.
Keywords: Machinery; Efficiency; PerformanceTractor